Body fat distribution and risk of coronary heart disease in men and women in the European Prospective Investigation Into Cancer and Nutrition in Norfolk cohort: a population-based prospective study. - Canoy, D; Boekholdt, S; Wareham, N; Luben, R; Welch, A; Bingham, S; Buchan, I; Day, N; Khaw, K (2007)
BACKGROUND: Body fat distribution has been cross-sectionally associated with atherosclerotic disease risk factors, but the prospective relation with coronary heart disease remains uncertain. METHODS AND RESULTS: We examined the prospective relation between fat distribution indices and coronary heart disease among 24,508 men and women 45 to 79 years of age using proportional hazards regression. During a mean 9.1 years of follow-up, 1708 men and 892 women developed coronary heart disease. The risk for developing subsequent coronary heart disease increased continuously across the range of waist-hip ratio. Hazard ratios (95% CI) of the top versus bottom fifth of waist-hip ratio were 1.55 (1.28 to 1.73) in men and 1.91 (1.44 to 2.54) in women after adjustment for body mass index and other coronary heart disease risk factors. Hazard ratios increased with waist circumference, but risk estimates for waist circumference without hip circumference adjustment were lower by 10% to 18%. After adjustment for waist circumference, body mass index, and coronary heart disease risk factors, hazard ratios for 1-SD increase in hip circumference were 0.80 (95% CI, 0.74 to 0.87) in men and 0.80 (95% CI, 0.69 to 0.93) in women. Hazard ratios for body mass index were greatly attenuated when we adjusted for waist-hip ratio or waist circumference and other covariates. CONCLUSIONS: Indices of abdominal obesity were more consistently and strongly predictive of coronary heart disease than body mass index. These simple and inexpensive measurements could be used to assess obesity-related coronary heart disease risk in relatively healthy men and women.